Five-year library development plan for Palaris College in Pangasinan - Baun, Urduja S.; Atienza, Daisy B.; Muñasque, Narcissa V. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1979)
The Five-Year Library Development Plan of Palaris Colleges in Pangasinan is a study made for the purpose of reorganizing and developing the libraries of the college which have been ineefective and unmanageable for the past many years. It is also intended to serve as an instrument that will contribute to the accreditation of said institution in the near future.
The study consists of two parts. The first is the presentation of the findings and problems or the state or condition of the libraries of the college, and the second is the proposed five-year library development plan. This part of the study includes the recommendations and the suggested strategies which can be utilized in implementing the five-year plan.
Foremost among the various recommendations is the organization of the Palaris Colleges Library System (PCLS). This structural reorganization will unify the operations of the libraries under the administrative supervision of the PCLS Librarian or the Chief Librarian. The proposed PCLS will become one separate department in addition to the existing six departments, and as such, it can strengthen its linkages with the academic programs of the institution.
The proposed five-year library development plan takes off from the summary of findings of the functional analysis and proposal presented in Table 5. The scheme for the five-year library development plan is shown in Figure 3. The final chapter of the study elaborates on the findings, problems and recommendations and includes the proposed timetable for the implementation of PCLS activities/programs/projects.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Palaris College. Library